Friends, lovers, and the big terrible thing eaudiobook A memoir. - Perry, Matthew (Macmillan Audio, 2022)
"Going into his "why," Perry's audiobook is a fascinating listen."- AudioFile This program is read by the author. A MOST ANTICIPATED BOOK BY TIME, THE ASSOCIATED PRESS, GOODREADS, USA TODAY, AND MORE! The beloved star of Friends takes us behind the scenes of the hit sitcom and his struggles with addiction in this candid, funny, and revelatory memoir that delivers a powerful message of hope and persistence. "Hi, my name is Matthew, although you may know me by another name. My friends call me Matty. And I should be dead." So begins the riveting story of acclaimed actor Matthew Perry, taking us along on his journey from childhood ambition to fame to addiction and recovery in the aftermath of a life-threatening health scare. Before the frequent hospital visits and stints in rehab, there was five-year-old Matthew, who traveled from Montreal to Los Angeles, shuffling between his separated parents; fourteen-year-old Matthew, who was a nationally ranked tennis star in Canada; twenty-four-year-old Matthew, who nabbed a coveted role as a lead cast member on the talked-about pilot then called Friends Like Us . . . and so much more. In an extraordinary story that only he could tell—and in the heartfelt, hilarious, and warmly familiar way only he could tell it—Matthew Perry lays bare the fractured family that raised him (and also left him to his own devices), the desire for recognition that drove him to fame, and the void inside him that could not be filled even by his greatest dreams coming true. But he also details the peace he's found in sobriety and how he feels about the ubiquity of Friends , sharing stories about his castmates and other stars he met along the way. Frank, self-aware, and with his trademark humor, Perry vividly depicts his lifelong battle with addiction and what fueled it despite seemingly having it all. Friends, Lovers, and the Big Terrible Thing is an unforgettable memoir that is both intimate and eye-opening—as well as a hand extended to anyone struggling with sobriety. Unflinchingly honest, moving, and uproariously funny, this is the audiobook fans have been waiting for. A Macmillan Audio production from Flatiron Books.